Birthing centre infrastructure in Nepal post 2015 earthquake - Mahato, Preeti; Regmi, Pramod; van Teijlingen, Edwin; Simkhada, Padam; Angell, Catherine; Sathian, Brijesh (Nepal Journal of Epidemiology, 2015)
We suggest that a focus on improving facility delivery services starting from the most severely affected districts could be the necessary step towards achieving universal health care. Technical and financial support offered by international development partners can play a crucial role in enhancing the capabilities of health care facilities including birthing centres.